UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI MENGENAL LUAS BANGUN DATAR BERBANTU MEDIA POWTOON PADA PESERTA DIDIK KELAS V SD NEGERI 1 KARANGDUREN - Nugroho, Agung Wahyu; Arif Muat Julianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is investigated from the background of fifth grade students of SD Negeri 1 Karangduren experiencing difficulties in learning mathematics with flat area material. After observation or observation, in learning mathematics the teacher is still the only source of learning knowledge or it can be said that learning is still teacher-centered and the teacher does not use innovative learning media. This research uses the type of Classroom Action Research (PTK) to improve the learning outcomes of students on the material of recognizing the area of flat shapes with the help of powtoon media. This research. The subjects of this study were VA class students of SD Negeri 1 Karangduren in the 2023/2024 academic year, totaling 20 students. The research instruments in this study used tests, teacher and student observations and documentation. The results of this study show that powtoon can improve learning outcomes in fifth grade students of SD Negeri 1 Karangduren on the material of flat area. This is indicated by the results of observation of student activities with an average in cycle I of 62.86% with sufficient criteria and in cycle II obtained an average of 81.81% with excellent criteria.